How can we consider variable RBE and LETd prediction during clinical practice?: A pediatric case report at the Normandy Proton Therapy Centre using an independent dose engine - Mein, Stewart; Kopp, Benedikt; Vela, Anthony; Dutheil, Pauline; Lesueur, Paul; Stefan, Dinu; Debus, Jürgen; Haberer, Thomas; Abdollahi, Amir; Mairani, Andrea; Tessonnier, Thomas (Radiation oncology, 2022)
To develop an auxiliary GPU-accelerated proton therapy (PT) dose and LETd engine for the IBA Proteus®ONE PT system. A pediatric low-grade glioma case study is reported using FRoG during clinical practice, highlighting potential treatment planning insights using variable RBE dose (DvRBE) and LETd as indicators for clinical decision making in PT.